2018
DOI: 10.1002/ecy.2474
|View full text |Cite
|
Sign up to set email alerts
|

A reality check for climate change experiments: Do they reflect the real world?

Abstract: Experiments are widely used in ecology, particularly for assessing global change impacts on ecosystem function. However, results from experiments often are inconsistent with observations made under natural conditions, suggesting the need for rigorous comparisons of experimental and observational studies. We conducted such a "reality check" for a grassland ecosystem by compiling results from nine independently conducted climate change experiments. Each experiment manipulated growing season precipitation (GSP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 55 publications
3
45
1
Order By: Relevance
“…Therefore, we are confident that variation in GSP, and by extension water avail ability, was, and is, the dominant control on primary productivity dynamics within this grassland ecosystem, consistent with previ ous findings (Briggs & Knapp, 1995;Felton, Knapp, & Smith, 2019;Hoover et al, 2014a). Our work underscores the validity and com plimentary nature and utilizes longterm data to interpret ecological experiments (Knapp et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, we are confident that variation in GSP, and by extension water avail ability, was, and is, the dominant control on primary productivity dynamics within this grassland ecosystem, consistent with previ ous findings (Briggs & Knapp, 1995;Felton, Knapp, & Smith, 2019;Hoover et al, 2014a). Our work underscores the validity and com plimentary nature and utilizes longterm data to interpret ecological experiments (Knapp et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…In this study, our results showed clear evidence for the nonlinear BNPP-precipitation relationship (Fig. 3b; Appendix S1: Table S2), along with a similar nonlinear ANPP-precipitation relationship that has been frequently observed in previous studies (Bai et al 2008, Gherardi and Sala 2015, Zhang et al 2017c, Knapp et al 2018. As precipitation increased, the saturated response of soil environmental factors (mean and variability of soil-water content, soil temperature, and nitrogen availability) contributed to the nonlinear increase of ecosystem productivity.…”
Section: Nonlinear Response Of Npp and Its Allocation To Changing Presupporting
confidence: 88%
“…Even if some variables, such as ANPP of shallow-rooted species, showed increasing sensitivity to drought treatments over time, they seemed to be more attributed to the declining ambient precipitation. These results suggest that plants are much more responsive to the current changing precipitation rather than cumulative effects, indicating the validity of the experimental approach in studying the influence of changing precipitation on ecosystem functioning (Knapp et al 2018).…”
Section: Bnpp Vertical Redistribution Maintains Plants' Water Acquisimentioning
confidence: 85%
See 2 more Smart Citations